Aprendizaje significativo de las operaciones con fracciones en estudiantes de básica primaria según opiniones de docentes : Meaningful learning of operations with fractions in primary school students according to the opinions of teacher - Rocha Flórez, Juan José; Padilla Escorcia, Iván Andrés; Miranda Zapata, Orlando Miguel (Encuentro Educacional, 2024)
Meaningful learning encompasses a series of cognitive, affective, and social processes that are activated in the subject’s mind to relate new knowledge to the previous information that they handle in their daily lives. It is essential for a lasting appropriation of knowledge in all areas of human activity and, especially, in mathematics, since in this discipline abstract knowledge is handled that must be extrapolated to situations and problems in the environment. The objective of this article is to analyze the opinion that teachers have in relation to the meaningful learning of operations with fractions in primary school students. It is based on contributions from Ramírez and Olmos (2020), Botero et al. (2017), Capilla (2016), among others. A qualitative study was carried out with 5th grade students and teachers from 3 institutions in the Repelón municipality, Atlántico department, Colombia. Through direct observation of the actors’ performance, it was possible to verify deficiencies in the appropriation of the concept of fractions that are manifested in practice when carrying out exercises with these operations. The interview technique was applied, with an instrument of 4 questions to 3 teachers, and it was possible to verify that, for them, there is no significant learning of fractions by the students, which makes it difficult for them to appropriate other content related to these operations at successive levels of schooling.